Sistem Pewarisan Hukum Adat Suku Moi Di Kota Sorong - Markus, Dwi Pratiwi; Mahmudah, Masrifatun; Islamiaty, Nurul (JUSTISI, 2022)
Customary law is one of the laws that is still firmly enforced in Sorong City, West Papua, the Moi Tribe is one of several tribes in Sorong City and is a tribe that is still thick in the customary law inheritance system. The position of sons and daughters in the customary law inheritance system of the Moi tribe is often a matter of debate, because looking at the customary law system that applies in Papua, it still uses the Patriarchal system but is also based on family law.            This research is empirical research, namely legal research by using field data as primary data sources, such as the results of interviews, observations and documentation. Then it is supported by secondary data, namely articles, journals and previous research.            The results of this study indicate that: 1). The Customary Inheritance System in the MOI Tribe gives equal status to men and women as heirs, but there are differences in the distribution of inheritance. 2). The difference in the position of female heirs and male heirs is caused by the MOI Indigenous Community adhering to the principle of patriarchy, namely, men are the first heirs and women are the second heirs.